The fast : the history, science, philosophy, and promise of doing without - Oakes, John, 1961- (Avid Reader Press, 2024)
"An engaging exploration of the unique history and biology of fasting--an essential component of many traditional health practices, religions, and philosophies, resurging in popularity today--perfect for readers of Breath by James Nestor and Why We Sleep by Matthew Walker. We fast all the time, even when we're not conscious of doing so. A fast manifests the idea of holding back, resisting the animal impulse to charge ahead. Its flip side is similarly everywhere: call it splurging, self-indulgence, or a variant of "self-care." Based on extensive historical, scientific, and cultural research and reporting, The Fast illuminates the numerous facets of this act of self-deprivation. John Oakes interviews doctors, spiritual leaders, activists, and others who guide him through this practice--and embarks on fasts of his own--to deliver a book that supplies readers curious about fasting with profound new understanding, appreciation, and inspiration. Fasting has become increasingly popular for a variety of reasons--from health advocates who see fasting as a method to lose weight or to detox, to the faithful who fast in prayer, to seekers pursuing mindfulness, to activists using hunger strikes as an effective means of peaceful protest. Fasting is central to holy seasons and days such as Lent in Christianity, Ramadan in Islam, and Yom Kippur in Judaism. Advocates for justice who have waged hunger strikes include Gandhi in India, Bobby Sands in Ireland, and the Taxi Workers Alliance in New York City. Whether for philosophical, political, or health-related reasons, fasting marks a departure from daily routine. Fasting involves doing less but doing less in a radical way, reminding us that a slower, more intentional contemplative experience can be more fulfilling. Ultimately, this book shows us that fasting is about much more than food: it is about reconsidering our place in the world"--